The correlation between serum protein Bcl-2 and caspase 3 levels as a risk factor in abortion - Herlambang Noerjasin (Indonesian Journal of Obstetrics and Gynecology, 2010)
Objective: To determine the correlation between serum protein Bcl-2 with caspase-3 levels on normal pregnancy and abortion, and the strength of serum protein Bcl-2 with caspase-3 levels as means for diagnostic test. Methods: A case control study was carried out. Samples were obtained from the serum of incomplete abortion patients and normal pregnancy as control. Serum protein Bcl-2 and caspase-3 levels were examined with ELISA method. Result: Mean Bcl-2 level in subjects with abortions is 7.263 (SD 1.71) ng/ml, lower than normal pregnancies, which is 7.490 (SD 3.938) ng/ml, with significant different (p=0.050). Mean caspase-3 in subjects with abortions is 112.74 (SD 152.73) mg/ml, higher than normal pregnancies, which is 14.94 (SD 23.18) mg/ml, with significant different (p